PERSEPSI MAHASISWA TERHADAP SENI RUPA TRADISI DAN KONTEMPORER SERTA RELASI PROSES PENJELAJAHAN IDE KREATIF DALAM BERKARYA - Afatara, Narsen; Adi, Sigit Purnomo; Mataram, Sayid; Prameswari, Nadia Sigi (Institut Seni Indoensia Surakarta, 2018)
ABSTRACTThe essence of art is creating beauty. Since ancient times beauty is something that is always sought after by humans. The beauty is getting worse due to traditional art increasingly abandoned. Traditional art is all things related to values in a particular community which are maintained purely from generation to generation. In contrast to contemporary art, one of the most prominent and prominent characteristics in contemporary art is the disappearance of boundaries between art. Both forms and styles of fine arts need to be preserved by students as the next generation. The importance of preserving art is part of the preservation of the arts and culture of the nation's heritage. Traditional and contemporary art are taught in the realm of education, especially at the university level through fine arts courses. The purpose of this study is to find out the perceptions of art students on traditional art and contemporary art, so that students as young people can identify and determine their interest in one form and style between traditional and contemporary art.Â Keywords: Fine Art, Contemporary and Traditional